Industrial Clusters and Micro and Small Enterprises in Africa : From Survival to Growth. - Bank, World (Directions in Development., 2010)
The World Bank, Japan International Cooperation Agency (JICA) Research Institute, and the Foundation for Advanced Studies on International Development (FASID), in collaboration with researchers affiliated with the African Economic Research Consortium (AERC), recently conducted a study on Africaâ??s domestic enterprises to improve the understanding of the constraints micro and small enterprises in Africa face in improving productivity and expanding their markets. In Africa, there are stark performance gaps between domestically owned enterprises and foreign-owned enterprises in terms of sales pe.